Time-dependent vibrational sum-frequency generation spectroscopy of the air-water interface - Ojha, Deepak; Kaliannan, Naveen Kumar; Kühne, Thomas D. (Communications Chemistry, 2019)
Vibrational sum-frequency generation spectroscopy is a powerful method to study the microscopic structure and dynamics of interfacial systems. Here we demonstrate a simple computational approach to calculate the time-dependent, frequency-resolved vibrational sum-frequency generation spectrum (TD-vSFG) of the air-water interface. Using this approach, we show that at the air-water interface, the transition of water molecules with bonded OH modes to free OH modes occurs at a time scale of 3 ps, whereas water molecules with free OH modes rapidly make a transition to a hydrogen-bonded state within 2 ps. Furthermore, we also elucidate the origin of the observed differential dynamics based on the time-dependent evolution of water molecules in the different local solvent environments.
CRIS-Team Scopus Importer:2023-03-20